Lojalitetspliktens gränser i den privata sektorn - Med fokus på konkurrerande verksamhet och kritikrätt - Bommarco Hennius,Alba; Larsson,Hanna (2026)
This thesis analyzes the duty of loyalty of private-sector employees in the employment relationship, with a focus on competing activities and the exercise of the right to criticize. Using a descriptive doctrinal method, the study examines the applicable law primarily through case law from the Swedish Labour Court, supplemented by statutes, preparatory works, and legal doctrine. The analysis shows that competing activities are typically considered a serious breach of loyalty when they cause or risk causing non-negligible harm. Such harm may be economic but can also involve a loss of reputation. Factors that are particularly relevant in the assessment include the nature and extent of the activity, the employee’s position and access to sensitive information, the employer’s business area, and the purpose of the activity. In the area of the right to criticize, no direct damage requirement is established, however, the criticism must be objective and aimed at addressing deficiencies or irregularities in the workplace. The assessment is influenced, among other things, by the context of the criticism, its content, and whether it was first raised internally. The employee’s position is also relevant in the evaluation. Furthermore, there may be a public interest in making the criticism public. The protection against retaliation under the Whistleblowers Act is therefore relevant in this context. In conclusion, a holistic assessment is required to determine whether an employee has breached their duty of loyalty.
Keywords: private-sector employees; duty of loyalty; competing activities; right to criticize; Swedish Labour Court; assessment criteria privatanställda; lojalitetsplikt; Arbetsdomstolen; bedömningskriterier konkurrerande verksamhet; kritikrätt